PENGARUH KEMAMPUAN MENGGAMBAR MOTIF TERHADAP HASIL BELAJAR KRIYA BATIK SISWA KELAS XI DI SMKN 8 PADANG - Vanesha Miswar (Educraf : Journal Of Craft Education, Craft Design And Creative Industries, 2022)
This research is a quantitative research. The data were analyzed using descriptive statistical analysis. This research aimed to determine the effect of ability to drawing motifs of class XI at SMKN 8 Padang and the factors that influence the ability to drawing motifs. The population in this research were students of class XI majoring in Textile Crafts department at SMKN 8. Meanwhile, the sample was selected based on "purposive sampling" which is taking samples based on special characteristics that are in accordance with the research objectives. Sample were 30 students of class XI from Textile Crafts department. The questionnaire is used to collect the data. Questionnaires are arranged based on the variable of drawing ability, the motives are described based on variable indicators, then developed into items of questions. While the data's achievement are taken by teacher subject in final grade documentation. The results of this study indicate that the relationship between the ability to draw motifs with batik craft learning outcomes is significant. The average score of ability to drawing motifs (3.00) while the average score of learning achievement (3.00).